2010
DOI: 10.1111/j.1365-2230.2009.03437.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative protein damage and antioxidant status in systemic lupus erythematosus

Abstract: The findings suggest that protein oxidation may play a role in the pathogenesis of chronic organ damage in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 23 publications
1
35
1
Order By: Relevance
“…In our study, SH group levels were found to be signifi cantly decreased in SLE patients compared to normal controls (260.2 ± 182.7 versus 339.4 ± 104.3 µmol/L), similar to the report of Zhang et al 25 This supports the role of oxidative stress in the pathogenesis of SLE.…”
supporting
confidence: 92%
“…In our study, SH group levels were found to be signifi cantly decreased in SLE patients compared to normal controls (260.2 ± 182.7 versus 339.4 ± 104.3 µmol/L), similar to the report of Zhang et al 25 This supports the role of oxidative stress in the pathogenesis of SLE.…”
supporting
confidence: 92%
“…Our data further agree with the results found by Zhang et al in plasma of SLE patients. 48 In the present study, the overall oxidative status was mostly evaluated in WBCs, instead of plasma. Thus, our results confirm previous studies and show that oxidative stress is further promoted in circulating WBCs, including monocytes and neutrophils of APS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Severity of the disease might be enhanced by the imbalance between oxidative stress and helper T-cell (Th1)-derived cytokines in SLE [15]. The SLEDAI correlates with serum markers of oxidant stress in SLE [18] and correlated negatively with levels of GSH and GSH Px [16] which may aid in the evaluation of treatment effectiveness [7]. It is suggested that in active SLE, oxidative status is increased without a corresponding elevation of the antioxidants, which verifies the value of using potent antioxidant therapy in preventing oxidative damage in SLE [19].…”
Section: Calculationmentioning
confidence: 97%
“…Px, and antioxidant molecules such as GSH are significantly reduced in erythrocytes [15,16] and lymphocytes [17], and the levels of lipid peroxidation, measured as MDA, are significantly higher in SLE patients [5,15].…”
Section: Calculationmentioning
confidence: 99%